2013
DOI: 10.1007/s00540-013-1650-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidences and predictors of difficult laryngoscopy in adult patients undergoing general anesthesia

Abstract: The results indicate that the risk for difficult airway situations might substantially differ between surgical patient groups. In hospitals with departmental structures and spatially separated operating rooms, the deduction might be increased awareness and particular structural preparation for difficult airway situations in the respective subspecialties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 41 publications
(28 reference statements)
2
49
2
3
Order By: Relevance
“…2,27 Redundant mucosal tissues hampering glottic visualization may explain this finding in both techniques.…”
Section: Discussionmentioning
confidence: 90%
“…2,27 Redundant mucosal tissues hampering glottic visualization may explain this finding in both techniques.…”
Section: Discussionmentioning
confidence: 90%
“…Heinrich et al [11] reported that male gender as a risk factor for C-L grade III/IV findings. In this study, male gender was higher incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Heinrich et al [11] reported that 6.1% of Values are presented as number (%). [11] reported that 17.3% of DI cases had Mallampati scores of III or IV and that the Mallampati score was a factor that increased the predict rate for DI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk factors included age younger than 1 year (4.7 versus 0.7%), ASA class 3 and 4, a higher Mallampati class (3 and 4), a lower BMI, and patients undergoing oral and maxillofacial surgery or cardiac surgery. For comparison, the same authors reviewed the anesthetic airway management in a cohort of 102 305 adults [12]. The overall rate of difficult laryngoscopy was 4.9%, more than 3 times that noted in the pediatric population.…”
Section: Key Pointsmentioning
confidence: 98%